2015
DOI: 10.2463/mrms.2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

MR-based Computational Fluid Dynamics with Patient-specific Boundary Conditions for the Initiation of a Sidewall Aneurysm of a Basilar Artery

Abstract: We performed 3-dimensional cine phase-contrast magnetic resonance-based computational fluid dynamics for a basilar artery that developed a sidewall aneurysm over a 25-month period. There was an area with high gradient oscillatory number in the location of the future aneurysm ostium and an area with high wall shear stress (WSS) and high spatial WSS gradient at the distal edge of the future aneurysm. These could be biomarkers for development of intracranial aneurysms.Keywords: computational fluid dynamics, hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A benefit of 4D‐Flow compared to vector flow mapping in echocardiography or 2D MR velocity mapping is the full 3D coverage of the heart and great vessels, and the feasibility of retrospective analysis of flow at any location . Thus, 4D‐Flow can provide information on flow dynamics, in addition to morphological and functional parameters, of the LV in a noninvasive and comprehensive manner, and it has the potential to allow detection of flow dynamic factors related to the initiation or progression of various heart and vessel diseases …”
Section: Discussionmentioning
confidence: 99%
“…A benefit of 4D‐Flow compared to vector flow mapping in echocardiography or 2D MR velocity mapping is the full 3D coverage of the heart and great vessels, and the feasibility of retrospective analysis of flow at any location . Thus, 4D‐Flow can provide information on flow dynamics, in addition to morphological and functional parameters, of the LV in a noninvasive and comprehensive manner, and it has the potential to allow detection of flow dynamic factors related to the initiation or progression of various heart and vessel diseases …”
Section: Discussionmentioning
confidence: 99%
“…Since blood flow at any cross section of a vessel can be calculated using 3D cine PC MR images, the information acquired can be utilized as boundary conditions in the analysis of computational fluid dynamics. 4,9,10…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we applied the flow rate reported by Ford et al [17] as the inflow boundary condition; however, a more realistic reproduction of the aneurysm hemodynamics mandates the application of patient-specific conditions. The flow velocity parameters for these conditions can be derived from patient clinical images, such as magnetic resonance images or angiograms [40,41]. Additionally, considering that the outflow condition is believed to influence the local hemodynamics, the related parameters should also be patient specific [42][43][44].…”
Section: Limitations and Future Workmentioning
confidence: 99%